Trade and inclusive growth - Bacchetta, Marc,Cerra, Valerie,Piermartini, Roberta,Smeets, Maarten (International Monetary Fund, 2021)
This paper surveys the literature on the relationship between international trade and inclusive growth. It examines claims that the rise in inequality in many countries can be attributed to the concurrent rise in trade competition, especially from EMEs like China, spurring trade tensions and protectionist measures. The paper investigates the conflicting literature showing the aggregate benefits of trade versus the adverse and persistent impact of trade, especially import competition, on specific industries and local communities. The paper then reviews the evidence for using trade policies and other complementary policies for adjustment and compensation to those groups adversely affected by trade
10.5089/9781513572734.001
Keywords: Graue Literatur; trade; inclusive growth; inequality; globalization; growth; poverty; gender; Globalization; Growth; Inclusive Growth; Inequality; Trade; labor; Economics: General; International Economics; Exports and Imports; Macroeconomics; Taxation; Trade: General; Globalization: General; Equity; Justice; Inequality; and Other Normative Criteria and Measurement; Trade Policy; International Trade Organizations; Wages; Compensation; and Labor Costs: General; Economic & financial crises & disasters; Economics of specific sectors; International economics; Labour; income economics; Public finance & taxation; Financial crises; Economic sectors; International trade; Imports; Labor; Tariffs; Taxes; Trade policy; Currency crises; Informal sector; Economics; Exports; Wages; Tariff; Commercial policy